2001
DOI: 10.1016/s0895-7061(01)02140-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of ACE-inhibition and angiotensin II antagonism on fibrinolysis and insulin sensitivity in hypertensive postmenopausal women

Abstract: The aim of this study was to compare the effects of trandolapril and losartan on plasminogen activator inhibitor type 1 (PAI-1) levels and insulin sensitivity in hypertensive postmenopausal women. We studied 89 hypertensive (diastolic blood pressure >90 and <110 mm Hg) postmenopausal women, aged 51 to 60 years not taking any hormone replacement therapy. Diabetic, obese, and smoking patients were excluded. After a 4-week placebo period, they were randomized to receive 2 mg of oral trandolapril (n=45) or 50 mg o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
2
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 56 publications
3
46
2
7
Order By: Relevance
“…45,46,54 In the present study, imidapril significantly increased insulin sensitivity, as assessed by euglycemic-hyperinsulinemic clamp, whereas candesartan did not. These findings, which are in agreement with previous observations by ourselves and other authors, 35,[55][56][57] besides providing another possible explanation for the different effects of the two drugs on the fibrinolytic balance, also suggest that mechanisms other than Ang II inhibition, such as the increase in endogenous kinins because of ACE inhibition, might be responsible for the observed different influences of imidapril and candesartan on insulin sensitivity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…45,46,54 In the present study, imidapril significantly increased insulin sensitivity, as assessed by euglycemic-hyperinsulinemic clamp, whereas candesartan did not. These findings, which are in agreement with previous observations by ourselves and other authors, 35,[55][56][57] besides providing another possible explanation for the different effects of the two drugs on the fibrinolytic balance, also suggest that mechanisms other than Ang II inhibition, such as the increase in endogenous kinins because of ACE inhibition, might be responsible for the observed different influences of imidapril and candesartan on insulin sensitivity.…”
Section: Discussionsupporting
confidence: 93%
“…19,[29][30][31][32] Reasons for such different findings might be because of differences in experimental models, study population characteristics, duration of treatment and possible methodological bias. Some direct comparisons on the effects of ACE-Is and ARBs on plasma PAI-1 and t-PA have been performed, and again the results were controversial: [33][34][35][36][37][38] Some studies have shown that both ACE inhibition and AT1 antagonism were associated with a significant improvement in plasma fibrinolysis, 34 whereas others have observed a decrease in PAI-1 and/ or an increase in t-PA with ACE-Is but not with ARBs. 33,[35][36][37] Only a few studies have reported an improvement of fibrinolytic balance with ARBs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study irbesartan monotherapy did not significantly affect the fibrinolytic balance, thus confirming previous findings. [22][23][24][25][26][27] Possible explanations for the dissimilar effect of ACE inhibition and Ang II antagonism on PAI-1 levels might be that: (a) the endothelial receptors that mediate PAI-1 expression in response to Ang II are not type I receptor subtypes, but rather the AT4 receptors, which specifically bind to the hexapeptide 3-8 fragment of Ang II, indicated as Ang IV; 41 (b) unlike ACE Inhibitors, Ang II antagonists have no effect on the endogenous kinins. 42 The addition of hydrochlorothiazide to irbesartan monotherapy produced a significant increase in PAI-1 activity, which confirms previous observations.…”
Section: Discussionmentioning
confidence: 99%
“…13 Variable effects have been reported for diuretics 14,15 and b-blockers, 16,17 whereas Ca-antagonists seem to be associated with an increase in plasma t-PA activity. 18,19 ACE inhibitors have been demonstrated to reduce plasma levels of PAI-1, [20][21][22][23][24] whereas contrasting results have been reported on the effects of the angiotensin II (Ang II) antagonists. [22][23][24][25][26][27] The aim of the present study was to evaluate the effects on plasma PAI-1 and t-PA activities of the combination of delapril, a nonsulphydryl, nonprolinic, lipophilic ACE inhibitor, with high affinity for the C-terminal site of ACE 28 with manidipine, a second-generation, lipophilic dihydropyridine Caantagonist, with good efficacy/tolerability profile 29 as compared to the combination of the Ang II AT1 receptor antagonists irbesartan with hydrochlorothiazide in the treatment of hypertensive patients with type II diabetes mellitus, a population with a great impairment of the fibrinolytic function.…”
Section: Introductionmentioning
confidence: 99%